(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The tax system of the Republic of Uzbekistan, like all other systems, was established within the framework of scientifically based experiments developed in accordance with foreign experience and the opinions of scientists. We can quote the opinions of several scientists in this regard.